2022
DOI: 10.1021/acsomega.2c04628
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal Stability, and Flame Retarding Properties of Phosphorus-Modified PET Blended with DOPO-POSS

Abstract: In this study, an antidroplet flame retardant system based on FRPET (phosphorus-containing copolyester) is constructed with DOPO-POSS (polyhedral oligomeric silsesquioxane containing DOPO) as an additive flame retardant. It is demonstrated that DOPO-POSS has good dispersibility at a lower amount. When the amount of DOPO-POSS is 9 wt %, the residual char of DOPO-POSS/FRPET at 700 °C increases to 23.56 from 18.16% of FRPET, and the maximum thermal weight loss rate also reduces. What is more is that the limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…By analytical fitting, the P2p XPS of 3%BNNS@DOPA/PBS (Figure 10c) has two fitted peaks at 133.4 and 134.7 eV, representing OPO and PO 3 , primarily originating from metaphosphoric and phosphoric acids. The decomposition of the DOPO chain segment produces phosphoric acid 38 . Compounds like metaphosphoric acid coat the PBS surface, facilitating matrix dehydration for carbon formation.…”
Section: Resultsmentioning
confidence: 99%
“…By analytical fitting, the P2p XPS of 3%BNNS@DOPA/PBS (Figure 10c) has two fitted peaks at 133.4 and 134.7 eV, representing OPO and PO 3 , primarily originating from metaphosphoric and phosphoric acids. The decomposition of the DOPO chain segment produces phosphoric acid 38 . Compounds like metaphosphoric acid coat the PBS surface, facilitating matrix dehydration for carbon formation.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR and SEM analysis of PS 148 -Br and PS- b -PFAA-DOPO after combustion showed that the FAA-DOPO block was introduced into the polystyrene macromolecular chain; during the combustion of PS- b -PFAA-DOPO, the DOPO groups degrade to produce phosphoric acid and polyphosphoric acid, which can accelerate the dehydration of polystyrene and promote the carbonization behavior of polystyrene. Meanwhile, the PO· and PO 2 · radicals produced by the combustion of DOPO groups capture the flame propagating radicals (H· and HO·) to achieve the purpose of flame retardant. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…This material can be chemically or physically blended with the polymer matrix 38,39 . In recent years, the incorporation of POSS into the rubber and thermosetting polymers has been reported by some researchers 11,40–42 . Zhao, et al reported chemically incorporating 2.5% phenyl‐vinyl‐POSS into polydimethylsiloxane (PDMS), which ameliorated the tensile strength from 0.2 to 0.27 MPa and elongation at break from 14% to 123.6%.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In recent years, the incorporation of POSS into the rubber and thermosetting polymers has been reported by some researchers. 11,[40][41][42] Zhao, et al reported chemically incorporating 2.5% phenyl-vinyl-POSS into polydimethylsiloxane (PDMS), which ameliorated the tensile strength from 0.2 to 0.27 MPa and elongation at break from 14% to 123.6%. Also, it was reported that the initial decomposition temperature of silicone rubber augmented from 344.1 to 344.4 C. 43 Thermal stability and curing kinetics of benzoxazine composites reinforced by POSS, carbon nanotubes (CNT), and clays have been investigated by Lin et al Their results showed that incorporating POSS into BZ resin hindered network formation and enhanced the thermal stability of BZ resin; however, the clay enhanced the rate of the crosslinking reaction of BZ resin, especially at the beginning and after the middle of the crosslinking process.…”
mentioning
confidence: 99%